Modern possibilities of tear film stability restoration - V.V. Brzheskiy; G.G. Кim; V.А. Bobryshev (РМЖ "Клиническая офтальмология")
V.V. Brzheskiy, G.G. Кim, V.А. Bobryshev St. Petersburg State Pediatric Medical University, St. Petersburg, Russian Federation The pathogenetic basis of therapy for patients with dry eye syndrome consists of measures aimed at precorneal tear film restoration, including deficiency compensation of its lipid layer and aqueous mucin layer (with aqueous and mucin components) respectively. Among the numerous medications, artificial tear substitutes based on the sodium hyaluronate are drawing increasing attention. They differ from other lacrimal substitutes by their high hygroscopicity, thixotropy, mucomimeticity and other metabolic properties (biocompatibility, biodegradability, nonimmunogenicity, anti-inflammatory and regenerative activity, etc.). One of the ways to increase the viscosity, ocular surface stability and humectant duration is the cross-linking of hyaluronic acid using so-called "cross-linking agents" (carbodiimide hydrochloride, urea, divinyl sulfone, thiol-ene reaction, etc.). In vitro and in vivo experiments have proven the possibility of using such modified hyaluronic acid as an artificial tear substitute. The article presents a case study of a patient — a student suffering from computer vision syndrome who unsuccessfully used low viscosity tear substitutes while working at a computer. The use of cross-linked sodium hyaluronate 0.2% (hyaluronic acid sodium salt) in the background mode "by feeling" and at intervals of every 1.5 hours while working at the computer, significantly improved the condition of the patient's ocular surface and increased the duration of his "asymptomatic" time working at the computer. Keywords: dry eye syndrome, cross-linked hyaluronic acid, treatment efficacy. For citation: Brzheskiy V.V., Кim G.G., Bobryshev V.А. Modern possibilities of tear film stability restoration. Russian Journal of Clinical Ophthalmology. 2024;24(3):151–157 (in Russ.). DOI: 10.32364/2311-7729-2024-24-3-7.